MONITORING DASHBOARD OF THE LOGISTICS SYSTEM STATE OF UKRAINIAN AGRO-TRADING UNDER CONDITIONS OF TURBULENCE (Development Service Industry Management, 2025)
The article explores the conceptual and applied foundations for developing a monitoring dashboard for the logistics system of Ukrainian agro-trading under conditions of external turbulence. The relevance of digital monitoring is substantiated as a tool to enhance the resilience and adaptability of logistics processes amid challenges caused by military conflicts, infrastructure disruptions, energy shortages, and global supply chain disturbances. The study analyzes current challenges affecting the functioning of transport, storage, and information-communication subsystems within agro-logistics.Based on a systemic approach, key logistics indicators necessary for operational management in turbulent conditions are identified. The role of Business Intelligence (BI) platforms, such as Power BI, Tableau, and Qlik, is examined in terms of integrating heterogeneous data sources, ensuring transparency of processes, and supporting predictive analytics. The article proposes a structured monitoring dashboard comprising five interconnected blocks: transportation accessibility, storage infrastructure, operational risks, energy supply, and digital interaction. Each block reflects critical aspects of logistics performance, enabling real-time assessment and comprehensive situational awareness.The study highlights the importance of interactive, adaptive, and user-customizable interfaces, as well as integration with corporate and governmental information systems, to create a unified logistics information environment. Practical examples from Ukrainian agro-trading companies demonstrate that implementing monitoring dashboards allows for timely detection of bottlenecks, optimization of transport routes, improved warehouse utilization, and faster response to disruptions in energy or supply chains.The article concludes that deploying monitoring dashboards is a key element of digital transformation in agro-logistics, increasing the transparency, efficiency, and resilience of the logistics system. Such tools facilitate informed decision-making at various management levels, minimize risks and losses, and ensure continuity of supply chains under turbulent conditions. The study underscores the potential for future integration of monitoring systems with artificial intelligence algorithms to enhance predictive capabilities and further strengthen the competitiveness of the Ukrainian agro-trading sector in domestic and international markets.
Keywords: logistics system; agro-trading; monitoring dashboard; agricultural logistics; digitalization; turbulence; logistics indicators